Possible Influence of Resistance to Malaria in Clinical Presentation of Rheumatoid Arthritis: Biological Significance of Natural Selection. (14th November 2012) - Bonilla-Abadía, Fabio; Tobón, Gabriel J.; Cañas, Carlos A.
Abstract : Rheumatoid arthritis (RA) is a common autoimmune disease that affects all ethnic groups. Genetic factors, mainly HLA alleles, are highly associated with increased risk to develop RA. However, there are few available data about the role of these genetic polymorphisms in the prevalence or severity of RA in the Afrodescendant population, who have evolutionarily and by natural selection developed mutations that allowed them to acquire resistance to infectious diseases like malaria. Some of the mechanisms, by which this resistance was developed as a product of natural selection, are involved in different forms of immunological response, many of them of a well-known importance in the pathophysiology of RA. This paper focuses on presenting the known mechanisms of resistance to malaria and their possible contribution to the pathophysiology of RA, including "loss-of-function" mutations, lack of expression of chemokine receptors, decrease of immune complexes clearance by asplenia, or increase of immune reactivity mediated by B cells, among other mechanisms in this special group of patients.